Some comments on the settlement of disputes within the WTO. - Espinoza Soto, Álvaro (Estudios Internacionales, 2009)
Many aspects of the Dispute Settlement System of the World Trade Organization (WTO) are worth studying. This article aims to analyze just some of those topics, in the context of public international law: the nature of the dispute; whether there is an exercise of a judicial function and whether it is appropriate to characterize it as a tribunal or court; and, whether a precedent is legally binding for future cases.